Beyond Disability Stigma: Examining Tolerance and Intolerance toward Disability Issues - Mark T. Carew; Tom Shakespeare (Scandinavian Journal of Disability Research, 2024)
Disability research has focused a lot on stigma but very little on situations where individuals express tolerance or intolerance toward disability issues. Recent advances from social psychology suggest that intolerance is conceptually distinct from stigma and prejudice and results from value-driven reasons to interfere with a person’s beliefs or practices that have little to do with their identity or characteristics like impairment. However, study of (in)tolerance has so far been neglected in the disability context. In this paper, we address this gap. We argue that studying disability-related (in)tolerance is crucial for understanding disability discrimination and designing interventions to combat it. Moreover, we assert that integrating a study of (in)tolerance alongside disability stigma will offer a richer understanding of disability issues like assisted dying, inclusive education, decent work and access refusals. We also consider what makes disability-related intolerance ‘unjustifiable’ or ‘justifiable’, whether disabled people can themselves express intolerance to disability issues and how far promoting tolerance toward disabled people is even a good thing.